" Gender, Power, and Media A Study of Japanese Advertising Discourse as a Source of Media Literacy in Education" - Wismadewi, I Gusti Agung Galuh; I Nengah Suandi; I Nyoman Sudiana; I Putu Mas Dewantara (Journal of Practice Learning and Educational Development, 2025)
This study explores the representation of gender and power in Japanese television advertisements through the lens of Norman Fairclough’s Critical Discourse Analysis (CDA), while highlighting its educational significance as a resource for media literacy. Advertisements, as a key part of popular media, are powerful agents in shaping public perceptions and cultural norms. Especially among students, who increasingly consume media content in their daily lives. The analysis of selected advertisements aired between 2020 and 2024 reveals a recurring pattern of gender stereotyping: men are typically portrayed as assertive, dominant decision-makers, while women are depicted in passive, supportive, or domestic roles. These portrayals are reinforced through both visual elements and linguistic choices that reflect deep-rooted ideological structures. From an educational perspective, such media texts offer valuable opportunities to teach students critical literacy skills, enabling them to deconstruct messages, question assumptions, and reflect on issues of gender equity and representation. Integrating media discourse analysis into classroom practice supports the development of socially aware learners who can engage with media thoughtfully and responsibly. The study underscores the importance of media literacy as a transformative tool in promoting critical thinking and fostering a more equitable understanding of gender in contemporary society.